Pedagogical conditions of improvement of personal abilities of pupils of different school age at physical training lessons. - Nechyporencko L.A (Kharkov National Pedagogical University, 2011)
It is considered the problem of creation of corresponding pedagogical conditions for improvement of personal abilities of pupils of average and senior school age at physical training lessons. The technique of improvement of personal abilities at physical training lessons is offered. Criteria of definition of levels of development personal abilities are developed. Pedagogical conditions which influence improvement of personal abilities of schoolboys at physical training lessons are described. Efficiency of pedagogical conditions and the offered technique of improvement of personal abilities is checked up.